Loss - Schaff, Barbara (Romanticism on the Net, 2023)
This article investigates the importance of loss in the Romantic period from two perspectives: as a philosophical concept that bears on Romantic linguistic theory and perceptions of history and in terms of particular objects that either bear traces of loss or point to or represent lost objects. Ruins are architectural signifiers of a Romantic feeling of the transience of time and nostalgic reminiscences of a bygone past. Bodies in particular open up a whole range of possible signification: dead poets’ hair functions as a relic-like fetish, manuscripts as tokens of a material testimony of the poet’s genius remind us of the connection between mind and text, and poets’ statues bear witness to the transformation of the living body into a lasting cultural monument. Loss often indicates not only material loss but also the loss of original meaning, when the semantic attribution of things changes through recontextualization or relocation. Finally, when thinking about what is deemed worthy of preservation for posterity (mostly objects connected with a famous person of the period), one also needs to reflect on what is not preserved. In the context of Romantic authorship, it is very often the material belongings of women writers that were lost. The article concludes with a case study of two German Romantic writers, Emilie von Berlepsch and Annette von Droste-Hülshoff, and discusses the lack of material representation of their lives and works in a museum context.